2022
DOI: 10.1111/ced.15146
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID-19 pandemic on Breslow thickness of tumours and provision of outpatient malignant melanoma services in an Irish dermatology centre

Abstract: Dupilumab as treatment for atopic dermatitis in a pediatric heart transplant patient: a case report. Dermatol Ther 2020; 33: e14018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The study selection process is summarized in Figure 1 . From a total of 466 records, 25 studies were incorporated in our data analysis models [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study selection process is summarized in Figure 1 . From a total of 466 records, 25 studies were incorporated in our data analysis models [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…We read with interest the recent article published in Clinical and Experimental Dermatology by Bowe et al ., 1 describing the impact of the COVID‐19 pandemic on malignant melanoma (MM) services in Ireland. We wish to add our experience of the impact of the COVID‐19 pandemic on MM services, and to highlight the value of the ‘number needed to treat’ (NNT) as a metric to further analyse this.…”
Section: Figurementioning
confidence: 99%
“…Bowe et al . 1 reported a 27% decline in PL referrals between 2019 and 2020, with continued decline through 2021. Although we observed a 58% decline in PL referrals during the initial containment and lockdown phase of the COVID‐19 pandemic in April 2020 compared with similar timeframe in April 2018, 2 we found that, as government restrictions eased, there was a five‐fold increase in PL referrals from April ( n = 17) to August ( n = 89) 2020 (Fig.…”
Section: Figurementioning
confidence: 99%